In vitro Antibacterial Activity of an FDA-Approved H+-ATPase Inhibitor, Bedaquiline, Against Streptococcus mutans in Acidic Milieus - Zhang, Meng; Yu, Wenqian; Zhou, Shujing; Zhang, Bing; Lo, Edward Chin Man; Xu, Xin; Zhang, Dongjiao (Frontiers in Microbiology, 2021)
Abstract Background: Dental caries is an acid-related disease. Current anti-caries agents mainly focus on the bacteriostatic effect in neutral environment, while do not target acid-resistant microorganisms related to caries in acidic milieus. Objectives: To assess the in vitro antibacterial activities of bedaquiline against oral pathogens in acidic milieus. Methods: Using Streptococcus mutans, Streptococcus sanguinis and Streptococcus salivarius to prepare the mono-/multiple- suspension and biofilm. The MIC and IC50 of bedaquiline against S.mutans were determined by the broth microdilution method. Bedaquiline were compared regarding: (i) The inhibitory activity in pH 4-7 and at different time points against planktonic and biofilm. (ii) The effect on the production of lactic acid, extracellular polysaccharide and pH of S.mutans biofilm. (iii) The cytotoxicity effects. (iv) The activity on H+-ATPase enzyme of S.mutans. Results: In pH 5 BHI, 2.5 mg/L (IC50) and 4 mg/L (MIC) of bedaquiline inhibited the proliferation and biofilm generation of S.mutans and Mix in a dose-dependent and time-dependent way, but it was invalid in neutral environment. The lactic acid production, polysaccharide production and pH drop range reduced with the incorporation of bedaquiline in pH 5 environment. Its inhibitory effect (>56 mg/L) against H+-ATPase enzyme in S.mutans, and its non-toxic effect (<10 mg/L) on periodontal ligament stem cells were also confirmed. Conclusions: Bedaquiline is efficient in inhibiting the proliferation and biofilm generation of S.mutans and other oral pathogens in acidic environment. Its highly targeted and non-cytotoxicity also promote its clinical application potential in preventing caries. Further investigation of its specific action sites and drug modification are warranted. Keywords: Caries, Antibacteria activity, Streptococcus mutans, Acid resistance bacteria, Acidic environment.